Internship as a Business Analyst and Product Manager at SELISE Digital Platforms - Kabir, Asif Mojtoba (Brac University, 2022)
This Internship Report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.